Determination of prevalence of factors associated with burnout among health professionals in Maseru District, Lesotho. - Tiam, Apploninaire (My University, 2012)
BACKGROUND: Burnout is a syndrome of emotional exhaustion, depersonalization and a sense of low personal accomplishment that leads to decreased effectiveness at work. The researcher has chosen this particular topic because of recent developments in Lesotho where HIV/AIDS care scale up has been shifted to the clinics. The primary health care staff is requested to take care of very sick patients that need more home care and more social support. This adds to the load of the already overstretched personnel. METHODS: A cross-sectional descriptive study was carried out among health professionals (doctors and nurses) working in public health institutions in Maseru district of Lesotho using anonymous self administered questionnaires. Data were captured electronically into Epi info version 6 and analysed using Stata version 10.0 and Epi info software to generate frequency tables, to test relationship between demographic data and burnout factors. RESULTS: 200 questionnaire were administered, 155 (77.5%) were filled by health care workers. The age of respondents ranged from 20 to 65 years with 85.6% of them being female, 92.8% were nurses, 11.2% doctors. Working index data analysis showed variable results with 81.8% disagreeing that there were enough staff to provide quality patient care, 78.1% disagreeing that there were enough staff to get the work done and 72.8% that they had opportunity to work on a highly specialized patient care unit. Importantly, 61% of respondents agreed that health care workers had good working relationship. Concerning burnout profile of respondents, 63.3% felt that they were emotionally drained while 79.7% felt used up at the end of work day. 79.3% of respondents obtained satisfaction from working with HIV patients although 60.8% found working with HIV patients emotionally draining. Concerning job satisfaction, 84.2% of respondents were not satisfied with their wage. Considering association between demographics and burnout factors, male respondents were significantly more worried about the risk of contracting HIV from patients (p-value 0.01). In addition, doctors were also worried about the risk of contracting HIV from patients (p-value 0.02). This same feeling was significant among respondents working in hospitals (p-value 0.00). Hospital based respondents were also significantly more emotionally drained from their work than those in health centres (p-value 0.01). CONCLUSION: Key factors associated with burnout in this population include young age, low staffing capacity, low wage and lack of appreciation by managers. Individuals, health facility managers and government should take necessary steps in addressing these factors and thus preventing further worsening of the situation.
Keywords: Burnout, Professional